Persistence: Model Asylum Narratives and a Recognizable ‘Transgenderness’ - Camminga, B. (ICI Berlin Press, 2025)
In recent years, autobiographical narratives by transgender migrants and refugees from Africa have emerged, such as Farah Abdi’s Never Arrive, Neo Sandja’s Right Mind, Wrong Body, and Rizi Xavier Timane’s An Unspoken Compromise. This chapter examines these texts’ geographical focus and the resurgence of the ‘wrong body’ trope, considering what the transgender asylum narrative offers to the ‘trans travel narrative’. A key difference is the lack of a safe return — what I term the ‘unsafe return’.
Keywords: Transgender refugee; Trans travel narrative; Trans autobiography; Wrong body narrative; Transgender Africa; SDG-5: Gender equality